Efeitos de um programa de exercícios para o complexo tornozelo-pé em aspectos clínicos, funcionais e biomecânicos da marcha em pessoas com osteoartrite do joelho - Dantas, Glauko André de Figueiredo (Universidade Federal de São Carlos, 2021)
The main purpose of this thesis was to evaluate the effect of a supervised foot-ankle exercise program on the clinical, functional and biomechanical aspects of gait in individuals with knee osteoarthritis (KOA). For this, this investigation was based on 3 papers. Study 1 was the randomized clinical trial (RCT) protocol of two parallel arms, prospectively registered, with an allocation ratio of 1:1 and blinding of the outcome evaluators, which aimed to investigate whether a foot-ankle exercise program improves knee pain, functionality, foot strength and kinematics, knee overload during gait, and reduces drug intake in individuals with KOA. Individuals with medial tibiofemoral KOA would be randomized into an intervention group that would perform the supervised foot-ankle exercise program for 8 consecutive weeks, three times a week, or a control group that would not perform foot-ankle exercises and would follow the usual care recommended by health teams. The primary outcome of the study was the pain domain of the Western Ontario McMaster Universities Osteoarthritis Index (WOMAC) questionnaire being assessed at baseline (T0), immediately after the end of treatment (T8) and eight weeks after the end of treatment (T16 - follow-up). The secondary outcomes included were the stiffness, function and total score domains of the WOMAC questionnaire, physical function, isometric strength of the foot muscles, foot kinematics and knee overload during gait, which would be analyzed following the principles of intention-to-treat and per protocol. Study 2 consisted of a feasibility study following part of the methodology proposed in Study 1, which aimed to assess the feasibility of a RCT evaluating the effects of 8 weeks of supervised foot-ankle exercises on clinical and functional aspects in individuals with KOA. Feasibility was assessed by contact, eligibility compliance, and weekly recruitment rates; exercise program attendance, dropout and retention rates; safety and satisfaction with the exercise protocol; and potential changes in the outcomes of pain, stiffness and function self-reported, and physical function of individuals who performed the supervised foot-ankle exercise program. Contact, eligibility fulfillment, and recruitment success rates were 57%, 19.5%, and 88%, respectively; attendance, dropout and retention rates were 88%, 20% and 73.3%, respectively. The exercise program was also considered satisfactory and safe by 97.3% and 73.3% of the individuals, respectively. Sixteen individuals with KOA who were randomly allocated to the intervention group demonstrated improvement in self-reported pain, stiffness and function, and in physical function. Therefore, an eight-week foot-ankle strengthening program was found to be feasible, safe, satisfactory, and improved knee pain, stiffness, and physical function in individuals with KOA. Study 3 aimed to investigate the efficacy of an 8-week foot-ankle exercise program, compared to not performing foot-ankle exercises and following usual care recommended by health teams, on pain and functionality in individuals with KOA, following part of the methodology published in the protocol for RCT (Study 1). 30 individuals with medial tibiofemoral KOA were randomly allocated to an intervention or control group, previously described, being evaluated at T0, T8 and T16 using the WOMAC questionnaire (pain domain - primary outcome; stiffness, function and total score domains - secondary outcomes) and of physical tests recommended by the OsteoArthritis Research Society International (OARSI): 30-s chair stand test, 9-step stair climb test and 40-m fast-paced walk test. The per protocol analysis with 24 individuals who completed at least 80% of the sessions and at least the T0 and T8 assessments was performed and showed a statistically significant improvement in the WOMAC pain domain of the intervention group compared to the control group (mean difference = 5.8 points; 95%CI = 2.4 – 9.2; p = 0.002). The difference remained after analysis of covariance (ANCOVA) considering sex, body mass index (BMI) and initial WOMAC pain score as covariates. Regarding the secondary outcomes, statistically significant differences were noticed in the function and total score domains of the WOMAC questionnaire, and in the 30-s chair stand and 9-step stair climb tests. Therefore, an 8-week foot-ankle exercise program, compared to not performing exercises for and following the usual care recommended by health teams, is effective in improving self-reported knee pain and function, and physical function. individuals with KOA.
Effects of an foot-ankle exercise program on clinical, functional and biomechanical of gait aspects in people with knee osteoarthritis
Keywords: Osteoartrite do joelho; Exercício físico; Pé; Dor; Biomecânica; Knee osteoarthritis; Physical exercise; Foot; Pain; Biomechanics; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL